MENIMBANG KONDISI KESEHATAN MENTAL EMOSIONAL REMAJA DI KOTA CIREBON - Maryati, Sri; Subhan (Jurnal An-Nufus, 2023)
This study aims to determine how the condition of mental health and emotional in adolescents in the city of Cirebon. This research uses a quantitative approach with descriptive analysis methods. Which will be held at Posyandu Remaja in Cirebon City in November-December 2023. The population in this study was 478 person of Cirebon City at Posyandu Remaja who were randomly taken. Data analysis uses univariate analysis to determine the frequency distribution and percentage of each variable in the study. The results showed that most respondents were in the normal range on the components of behavioral problems (62.1%), emotional problems (92.9%), peer problems (54.4%) and prosocial skills (83.5%), but there were also data that showed borderline and abnormal conditions. Respondents who have tiers Components of behavioral problems (62.1%), emotional problems (92.9%), peer problems (54.4%) and prosocial skills (83.5%), but there are also data that show borderline and abnormal conditions. Respondents who had a level of behavioral problems in the borderline category were 98 people (20.5%) and abnormal as many as 83 people (17.4%), who had a level of emotional problems in the borderline category as many as 22 people (4.6%) and abnormal as many as 12 people (2.5%), who had peer problems in the borderline category as many as 147 people (30.8%) and abnormal as many as 71 people (14.9%), While the prosocial ability of adolescents in the borderline category was 53 people (11.1%) and abnormal as many as 26 people (5.4%). These findings show that although most adolescents are in the normal category, there are still adolescents who have a risk for mental health and emotional